2023
DOI: 10.1002/ece3.9694
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast phylogenomics and the taxonomy of Saxifraga section Ciliatae (Saxifragaceae)

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 100 publications
(186 reference statements)
1
10
0
Order By: Relevance
“…Therefore, it is demonstrated that none of S. diversifolia , S. pseudohirculus , and S. sinomontana complexes are monophyletic in view of the conclusion of this work and Yuan et al. ( 2023 ). Meanwhile, S. pseudohirculus and many members of the S. diversifolia complex were also highly accepted as being clustered in a clade in her results.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…Therefore, it is demonstrated that none of S. diversifolia , S. pseudohirculus , and S. sinomontana complexes are monophyletic in view of the conclusion of this work and Yuan et al. ( 2023 ). Meanwhile, S. pseudohirculus and many members of the S. diversifolia complex were also highly accepted as being clustered in a clade in her results.…”
Section: Discussionsupporting
confidence: 65%
“…Yuan et al. ( 2023 ) reconstructed the phylogenetic relationship of sect. Ciliatae with complete chloroplasts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations